MANAGEMENT OF PYOGENIC GRANULOMA: CASE REPORT - Kirtika, Sheoran; Pardeep, Singh; Pradeep, Yadav; Gyanander, Attresh (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Pyogenic granuloma is a common benign mucocutaneous lesion occurring intra orally or extra orally.The exact etiopathogenesis is unknown , although contributory factors include trauma, inflammation andinfectious agents. Intraoral lesions are sometimes associated with pregnancy. Typically, pyogenicgranuloma presents as an exuberant, red painless mass that easily bleeds, ulcerates and grows rapidly andis frequently seen on the gingiva. Treatment is complete surgical excision of growth tissue. The conditionis frequently associated with recurrence, and has more predilections towards females. Here by, presentinga case of pyogenic granuloma in a 45 years old female patient having swelling in anterior region.Surgical excision was done as treatment of choice